Self-controlled video feedback facilitates the learning of tactical skills in tennis - van der Meer, B. R.; van den Hoven, M. A. C.; van der Kamp, J.; Savelsbergh, G. J. P. (Research Quarterly for Exercise and Sport, 2024)
Purpose This study aimed to examine the effect of self-controlled video feedback on the learning of tactical motor skills in tennis, and additionally, whether this was affected by learners` self-efficacy and self-regulative skills.